Targeting RFWD2 as an Effective Strategy to Inhibit Cellular Proliferation and Overcome Drug Resistance to Proteasome Inhibitor in Multiple Myeloma - Guo, Mengjie; Ding, Pinggang; Zhu, Zhen; Fan, Lu; Zhou, Yanyan; Yang, Shu; Yang, Ye; Gu, Chunyan (Frontiers in Cell and Developmental Biology, 2021)
The potential to overcome resistance to proteasome inhibitors is greatly related with ubiquitin-proteasome system during multiple myeloma (MM) treatment process. The constitutive photomorphogenic 1 (RFWD2), referred to an E3 ubiquitin ligase, has been identified as an oncogene in multiple cancers, yet important questions on the role of RFWD2 in MM biology and treatment remain unclear. Here we demonstrated that MM patients with elevated RFWD2 expression achieved adverse outcome and drug resistance by analyzing gene expression profiling. Moreover, we proved that RFWD2 participated in the process of cell cycle, cell growth and death in MM by mass spectrometry analysis. In vitro study indicated that inducible knockdown of RFWD2 hindered cellular growth and triggered apoptosis in MM cells. Mechanism study revealed that RFWD2 controlled MM cellular proliferation via regulating the degradation of P27 rather than P53. Further exploration unveiled that RFWD2 meditated P27 ubiquitination via interacting with RCHY1, which served as an E3 ubiquitin ligase of P27. Finally, in vivo study illustrated that blocking RFWD2 in BTZ-resistant MM cells overcame the drug resistance in a myeloma xenograft mouse model. Taken together, these findings provide compelling evidence for prompting that targeting RFWD2 may be an effective strategy to inhibit cellular proliferation and overcome drug resistance in MM.